Analisis Vegetasi Gulma Tanaman Mawar pada Lahan Dataran Tinggi dan Rendah - Tarigan, Puji Lestari; Fitrianti, Arfiana; Wardhana, Arya Wira; Gabrielle, Vanessa; Andisha, Syakila Irgi; Ayni, Nurul (J-Plantasimbiosa, 2025)
Weeds are one of the main inhibiting factors in the cultivation of ornamental plants, including roses, because they compete for nutrients, air and light. This research aims to inventory and analyze weed vegetation in lowland (Sidoarjo, 8 masl) and highland (Batu, 900–950 masl). The research method includes observation in sample plots measuring 1x1 meter with six plots at each location, followed by analysis using the Important Value Index (INP). The results show that in the lowlands, Teki weed (Cyperus rotundus L.) dominates with an INP of 191.27, while in the highlands, Jotang Kuda weed (Syndrella nodiflora) dominates with an INP of 52.08. These differences reflect the weed's adaptation to the environmental conditions of each location. Effective and sustainable weed control is very necessary to increase the productivity and quality of rose cultivation.